2018
DOI: 10.1111/jphp.12937
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene carbonate)-containing polylactic acid microparticles with rifampicin improve drug delivery to macrophages

Abstract: The inclusion of PEC in PLA microparticles increased the release of RF and the inhibitory effect against two bacteria species while displaying physical particle properties similar to PLA particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Because of the high content of polylactic acid in copolymer, RIF is encapsulated in micelles. And due to hydrophobic interaction, it is easily loaded into the hydrophobic core, with high drug solubility [ 20 , 21 ]. Previous research [ 22 ] has shown that the formation of HPMA-PLA-RIF copolymer micelles enhanced the efficacy of drugs, improved the solubility of drugs, and combated the resistance of tuberculostatics.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high content of polylactic acid in copolymer, RIF is encapsulated in micelles. And due to hydrophobic interaction, it is easily loaded into the hydrophobic core, with high drug solubility [ 20 , 21 ]. Previous research [ 22 ] has shown that the formation of HPMA-PLA-RIF copolymer micelles enhanced the efficacy of drugs, improved the solubility of drugs, and combated the resistance of tuberculostatics.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, polyesters based therapeutics gain success in improving chemotherapeutic efficacy, both in vitro and in vivo, and anti-inflammatory response for treatment of cancer (Hu and Zhang 2012) and inflammatory diseases (Danhier et al 2012) respectively in various administration routes. Bioinert and biodegradable PLA and PLGA drug carrier materials hold outstanding advantages, including (i) sustainable delivery (Mansor et al 2018), (ii) proper control of drug release kinetics (iii) diminished fluctuations of blood drug concentrations (Makadia and Siegel 2011), (iv) augmented cellular uptake of NPs via endocytosis (Bi et al 2016;Priemel et al 2018), (v) enhanced stability (Xiong et al 2016), (vi) optimal clinical utility (Lü et al 2009) and (vii) improved medication adherence (Liu et al 2006).…”
Section: Pla and Plga Based Mps And Nps Systems For Drug Deliverymentioning
confidence: 99%
“…Substantial research has been done to develop alveolar macrophage targeting for pulmonary delivery wherein the drugs are entrapped in polymers, copolymers and lipids. Such formulations include microparticles [6][7][8] , nanoparticles 5,9 , solid lipid nanoparticles 2 etc.…”
Section: Introductionmentioning
confidence: 99%